Dilemma and countermeasure of sustainable leadership in physical education development in southern rural Ningxia, China - Fu, Xiaoya; Zhu, Weiqiang (Frontiers in Psychology, 2022)
Globally, above 1.4 billion adults did not reach to the recommended level of physical education in their daily life, thus tripple intendent reforms proposed by the ministry of physical education for the development of the sporting leadership in schools, colleges and universities which is essentially important for the development of physical and mental health of the students. This paper analyzes the situation of lacking sustainable sporting leadership among other factors related to Physical Education (PE) resources in the southern areas of Ningxia. A mixed and multi-method approach was adopted to conduct the study. Firstly, an in-depth but an open-ended qualitative interview with the professionals was carried, followed by cross-sectional data were collected from the respondents in two districts of the southern mountainous area of Ningxia. Moreover, a case study was included to support the phenomenon from the contextual perspective. The study present that PE education needs a modernization and rejuvenation plan to link with PE development and its sustainable execution and implementation for the physical and mental development of the learners. Moreover, it is suggested to strengthen the development of physical education with/through the fields of regional integration of educational resources sharing, cultural elements and integration, latest technological tools, research-based and cultural supported curriculum, and endogenous strength construction to promote the development of school physical education. Furthermore, continuous monitoring and evaluation mechanisms need to be adopted to develop physical education in the region.